2005
DOI: 10.1002/ajh.20362
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thy‐1 expression and cell‐cycle distribution in human bone marrow hematopoietic progenitors

Abstract: Analysis of the relationship between Thy-1 expression and cell-cycle distribution of hematopoietic stem cells (HSCs) Lin-Thy-1 + fraction, loses Thy-1 expression during 6 days, and re-expresses Thy-1 for an additional 2 days. Cell-cycle analysis demonstrated that this unique subset contains abundant S/G 2 M cells. Thus, Thy-1 expression appears to be an indicator of cell-cycle phase in targeting HSC, which might serve in the cell subset best suited for gene transfer. Am.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The development of hepatocyte‐like cells in adherent cultures in the presence of puromycin was also corroborated by the expression of the specific gene marker of mature hepatocytes Tat [37, 63] and of the gene for the liver‐specific anion transporter LST‐1 [60]. On the other hand, gene and protein expression of progenitor cell markers that, besides hematopoietic and nonhematopoietic bone marrow cells [89, , , , 94], salivary gland [75], neurons [95, 96], and endothelial cells [97], are also typical for hepatoblasts (common progenitors for both hepatocytes and biliary epithelial cells) isolated from fetal liver [40, 74, 76, 77, 98], as well as for hepatic oval (progenitor) cells found in adult liver [70, , 73, 99], suggested the presence of precursor cells in the adherent culture. The profile of the expression of progenitor marker proteins in respect of the colony morphology (center/periphery) is in line with previously published data attributing CD34 and c‐Kit to early hepatocyte precursors [70, 71, 73] and ascribing Thy‐1 and Dlk to advanced differentiated hepatoblasts and fetal hepatocytes [74, 77].…”
Section: Discussionmentioning
confidence: 99%
“…The development of hepatocyte‐like cells in adherent cultures in the presence of puromycin was also corroborated by the expression of the specific gene marker of mature hepatocytes Tat [37, 63] and of the gene for the liver‐specific anion transporter LST‐1 [60]. On the other hand, gene and protein expression of progenitor cell markers that, besides hematopoietic and nonhematopoietic bone marrow cells [89, , , , 94], salivary gland [75], neurons [95, 96], and endothelial cells [97], are also typical for hepatoblasts (common progenitors for both hepatocytes and biliary epithelial cells) isolated from fetal liver [40, 74, 76, 77, 98], as well as for hepatic oval (progenitor) cells found in adult liver [70, , 73, 99], suggested the presence of precursor cells in the adherent culture. The profile of the expression of progenitor marker proteins in respect of the colony morphology (center/periphery) is in line with previously published data attributing CD34 and c‐Kit to early hepatocyte precursors [70, 71, 73] and ascribing Thy‐1 and Dlk to advanced differentiated hepatoblasts and fetal hepatocytes [74, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, human lung fibroblasts derived from patients with hypersensitivity pneumonitis and idiopathic pulmonary fibrosis (IPF) characterized by an increased proliferative capacity are also Thy-1 negative (Ramirez et al, 2011). In contrast, only a Thy-1-positive subset of CD34 + human bone marrow hematopoietic stem cells entered the cell cycle after cytokine stimulation, whereas the Thy-1-negative subset remained quiescent (Takeda et al, 2005). These data suggest different cell type-or contextdependent functions for Thy-1.…”
Section: Introductionmentioning
confidence: 93%
“…The levels of chimerism of these 2 subset fractions are similar under nonlimiting cell transplantation conditions, but a limiting dilution analysis revealed that HSCs are 5 times more abundant in the Thy-1 + fraction [211]. There are also reports demonstrating the generation of Thy-1 + cells from Thy-1 -cells [211,212]. However, Majeti et al [213] were able to establish a cell hierarchy, where Thy-1 + CD45RA -cells give rise to Thy-1 -CD45RA -cells that are, in turn, upstream of Thy-1 -CD45 + cells.…”
Section: Thy-1mentioning
confidence: 99%
“…A reduction in the number of hematopoietic colonies was observed when an anti-Thy-1 antibody was added to cultures of Thy-1 + cells, suggesting that it may be involved in the development of HSCs [209]. Thy-1 has also been proposed as a cell cycle status indicator based on the observation that only the Thy-1 + fraction enters the S/ G2/M-phases when cells are stimulated by cytokines [212].…”
Section: Thy-1mentioning
confidence: 99%